The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4337/ejeep.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

From the European Monetary Union to a euro–bancor: a stock–flow consistent assessment

Abstract: The crisis of the euro area has questioned the fairness, sustainability and viability of the current setting of the European Monetary Union (EMU). In this article we use a four-country stock–flow consistent (SFC) model in the tradition of Godley/Lavoie (2007a) to examine to what extent an adaptation to Europe of Keynes's plan of a clearing union with bancor balances could help reduce the imbalances that, at least in part, drove the eurozone into crisis. Our simulation experiments suggest that the implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The literature on TARGET2 has continued to evolve in a number of ways, especially with the advent of the Eurosystem's Asset Purchases Programmes (APPs) in 2014. There are econometric studies of how to interpret TARGET2 balances (Abad et al 2013;Auer 2014;Eisenschmidt et al 2017;Chmielewski and Sławiński 2019;Cheung, Steinkamp, and Westermann 2020), technical analyses considering how NCBs can exit the TARGET2 system (Papadia 2014;Malinen et al 2016), scholars analysing the TARGET2 system in relation to the 1944 Keynes Plan for an International Clearing Union (Lavoie 2015;Amato et al 2016;Barredo-Zuriarrain, Molero-Simarro, and Quesada-Solana 2016;Rossi 2016;Mazier and Valdecantos 2019;Kregel 2019), the TARGET2 system as a risk-sharing mechanism (Schelkle 2017), as well as sociological studies focusing on the conceptual ambiguities of the TARGET2 system and how individuals deal with it (Krarup 2016;Sahr 2019). However, we still lack a proper political economy account of the role that the TARGET and TARGET2 systems play for European monetary unification that includes the politics connected to their introduction, the institutional reality they have created, and the process of institutional transformation they have triggered.…”
Section: Figure 1-timeline Of European Monetary Integration and The T...mentioning
confidence: 99%
“…The literature on TARGET2 has continued to evolve in a number of ways, especially with the advent of the Eurosystem's Asset Purchases Programmes (APPs) in 2014. There are econometric studies of how to interpret TARGET2 balances (Abad et al 2013;Auer 2014;Eisenschmidt et al 2017;Chmielewski and Sławiński 2019;Cheung, Steinkamp, and Westermann 2020), technical analyses considering how NCBs can exit the TARGET2 system (Papadia 2014;Malinen et al 2016), scholars analysing the TARGET2 system in relation to the 1944 Keynes Plan for an International Clearing Union (Lavoie 2015;Amato et al 2016;Barredo-Zuriarrain, Molero-Simarro, and Quesada-Solana 2016;Rossi 2016;Mazier and Valdecantos 2019;Kregel 2019), the TARGET2 system as a risk-sharing mechanism (Schelkle 2017), as well as sociological studies focusing on the conceptual ambiguities of the TARGET2 system and how individuals deal with it (Krarup 2016;Sahr 2019). However, we still lack a proper political economy account of the role that the TARGET and TARGET2 systems play for European monetary unification that includes the politics connected to their introduction, the institutional reality they have created, and the process of institutional transformation they have triggered.…”
Section: Figure 1-timeline Of European Monetary Integration and The T...mentioning
confidence: 99%
“…They find that a multi-speed union produces better results compared to the one that based on the Euro. Mazier and Valdecantos (2019) use an open-economy SFC model to test the effects of Keynes' Bancor on the Euro Area. They find that "the implementation of Keynes' ideas may conduct European countries to a stronger and more sustainable growth cycle" (Mazier and Valdecantos 2019, p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of Keynes' plan on the European Monetary Union have been tested also by Mazier and Valdecantos (2019), who have developed their previous four‐country SFC model (Mazier & Valdecantos, 2015) for this purpose. Their simulation experiments suggested that “the implementation of Keynes” ideas may conduct European countries to a stronger and more sustainable growth cycle' (Mazier & Valdecantos, 2019, p. 8).…”
Section: Open Economy Models In the Sfc Literaturementioning
confidence: 99%